2016
DOI: 10.1093/jac/dkw185
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride/HDL ratio and its impact on the risk of diabetes mellitus development during ART

Abstract: High TRG/HDL ratio predicted risk of new-onset DM, independently of other traditional risk factors. Furthermore, our findings suggest that advanced hepatic fibrosis, estimated using the fibrosis-4 score, could provide an additional predictor for DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Squillace et al . 21 showed that high TG/HDL ratio increased the risk of NOD, independently of other traditional risk factors, supporting the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Squillace et al . 21 showed that high TG/HDL ratio increased the risk of NOD, independently of other traditional risk factors, supporting the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, using a retrospective study design, Squilace et al . 40 showed among PLH that an elevated TG/HDL-C ratio (>third quartile or 4.5) was an independent predictor of T2DM onset. The TG/HDL-C ratio could be used not only as indicator of a pro-atherogenic lipid profile, but also as a simple biomarker of insulin resistance.…”
Section: Discussionmentioning
confidence: 97%
“…We used TG:HDL‐C ratio and plasma ALT as surrogate markers of insulin resistance, as both predict type 2 diabetes in non‐HIV populations [29–32]. Also among PLWH, a high TG:HDL‐C ratio predicted new‐onset DM independently of traditional risk factors [14], and elevated ALT has been associated with a higher risk of diabetes [33]. In addition, the adjusted prevalence of IFG among PLWH (20.0%) was double that in the general population (9.8%) in our study, again implying a higher degree of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…We used fasting plasma triglycerides‐to‐HDL cholesterol ratio (TG:HDL‐C) and ALT as surrogate markers for insulin resistance. The conventional cut‐off values indicating insulin resistance with TG:HDL‐C ratio (mg/dL) are ≥ 3.75 for men and ≥ 3.0 for women [14,15]. As uncontrolled HIV infection increases TG and decreases HDL‐C concentrations, we performed a sensitivity analysis limited to subjects with viral load < 50 HIV RNA copies/mL.…”
Section: Methodsmentioning
confidence: 99%